2018
DOI: 10.6004/jnccn.2018.7059
|View full text |Cite
|
Sign up to set email alerts
|

The Adrenal Gland as a Sanctuary Site of Metastases After Pembrolizumab Treatment: A Case Series

Abstract: Therapeutic agents targeting the PD-1/PD-L1 axis have shown durable clinical responses in patients with various cancer types. Although objective responses are common, intrapatient heterogeneous responses have been described, and the mechanism for the different organ responses remains unknown. We present a series of patients in whom a lack of response was noted solely in the adrenal glands. This is the first case series describing 3 patients with heterogeneous patterns of response to pembrolizumab with progress… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 23 publications
1
23
1
Order By: Relevance
“…Few clinical case reports of ICI-treated solid tumors and surgical series of patients with melanoma suggest that adrenal glands might be a sanctuary for tumor cells. 7 No warning signal has been reported for patients with lung cancer, though. 3 Our case series with five tumor progressions limited to the adrenal glands in patients with MSI/ dMMR mCRC is striking since CRC involving adrenal glands is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Few clinical case reports of ICI-treated solid tumors and surgical series of patients with melanoma suggest that adrenal glands might be a sanctuary for tumor cells. 7 No warning signal has been reported for patients with lung cancer, though. 3 Our case series with five tumor progressions limited to the adrenal glands in patients with MSI/ dMMR mCRC is striking since CRC involving adrenal glands is uncommon.…”
Section: Discussionmentioning
confidence: 99%
“…Taken together, these findings suggest that the tissue-specific tumor microenvironment differs between various metastatic sites and between patients. [8][9][10] In line with these findings, Nguyen et al 11 reported a case series of 3 patients with progression of adrenal gland metastases (AGMs) despite objective responses to the anti-PD-1 therapy pembrolizumab in all other metastatic sites. This supports the hypothesis that certain tissues in the body may possess tissuespecific resistance mechanisms because of different tumor microenvironments.…”
Section: Introductionmentioning
confidence: 82%
“…However, as previous case reports and studies have shown, AGMs may present an obstacle for successful treatment of patients with advanced-stage disease. 11,18,23,24 We and others have hypothesized that the adrenal gland may serve as a so-called sanctuary site, as defined by their inherent immunosuppressive microenvironment, allowing the tumor to grow in an immunologically permissive milieu and limiting the efficacy of ICIs. To further investigate this, we performed a large, single-center, retrospective analysis of all patients with stage IV melanoma with and without an AGM who were treated with ICIs.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No systemic therapy was utilized in those cases ( 14 ). A recently reported series consisted of two melanoma cases, and one uterine carcinosarcoma case, presenting with adrenal residual metastasis after pembrolizumab ( 15 ). Local therapy was effective in treating adrenal lesions in these cases.…”
Section: Discussionmentioning
confidence: 99%